Citizen schools A practical guide to education for citizenship and personal development - Alexander, Titus
Becoming a Citizenship School is a natural next step for schools wanting to motivate and equip young people for life in our complex society argues Titus Alexander in this practical guide. With photocopiable activities, extensive resource section and case studies showing how many schools are already making citizenship an every day experience for young people, the book is a must for those wanting to go beyond the citizenship curriculum in schools. Citizenship Schools is a practical guide to education for citizenship and personal development